2020
DOI: 10.3390/diagnostics10100777
|View full text |Cite
|
Sign up to set email alerts
|

Altered Regional Cerebral Blood Perfusion in Mild Cognitive Impairment Patients with Dizziness

Abstract: Dizziness is a common symptom among the general population, especially in the elderly. Previous studies have reported that dizziness may be associated with various cognitive functions including memory impairment. However, few studies have investigated the neural correlates of dizziness in patients with cognitive impairment. The aim of this study was to examine regional cerebral blood flow (rCBF) in mild cognitive impairment (MCI) patients with or without dizziness using single photon emission computed tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The left entorhinal cortex decreases in volume and cognitive and motor dysfunction in older adults with mild cognitive impairment (Sakurai et al, 2019). Cerebral blood flow (rCBF) in the left lateral orbital gyrus was decreased in the dizzy MCI group compared with the non-dizzy MCI group (Na et al, 2020). In an ALFF-based fMRI study, researchers found significantly increased ALFF values in the right lingual gyrus of MCI patients compared with HC (Lai et al, 2022).…”
Section: Key Regions Of Interests and Genes Selectionmentioning
confidence: 99%
“…The left entorhinal cortex decreases in volume and cognitive and motor dysfunction in older adults with mild cognitive impairment (Sakurai et al, 2019). Cerebral blood flow (rCBF) in the left lateral orbital gyrus was decreased in the dizzy MCI group compared with the non-dizzy MCI group (Na et al, 2020). In an ALFF-based fMRI study, researchers found significantly increased ALFF values in the right lingual gyrus of MCI patients compared with HC (Lai et al, 2022).…”
Section: Key Regions Of Interests and Genes Selectionmentioning
confidence: 99%